Selenium and Bacillus proteolyticus SES synergistically enhanced ryegrass to remediate Cu–Cd–Cr contaminated soil. (15th April 2023) - Nie, Min; Wu, Chihhung; Tang, Yanni; Shi, Guangyu; Wang, Xu; Hu, Chengxiao; Cao, Jun; Zhao, Xiaohu
Abstract: Heavy metal compound contaminated soil is an ecological threat, and soil containing copper (Cu), cadmium (Cd) and chromium (Cr) simultaneously is widely distributed. The application of phytoremediation in heavy metal combined contamination is still limited. In this study, to explore whether and how exogenous selenium (Se) and Bacillus proteolyticus SES enhance the remediation of combined Cu–Cd–Cr contaminated soil by ryegrass, pot experiments were carried out. Se alone or in combination with B. proteolyticus SES treatment increased the removal rates of heavy metals in the rhizosphere soil by 17.38%–157.25% relative to the control, while Se + B. proteolyticus SES treatment played a greater role in improving the heavy metals tolerance of ryegrass and increasing the activity of soil acid phosphatase. Moreover, Se and B. proteolyticus SES favored the preferential recruitment of specific taxa with the capacity of plant growth promotion and heavy metals resistance to the rhizosphere. The rhizosphere soil of Se treatment was specifically enriched with Lysobacter, Rhodanobacter, Micrococcales, Paenarthrobacter, and Adhaeribacter, while from class Bacilli to genus Bacillus enriched extensively and specifically in the rhizosphere of B. proteolyticus SES + Se treatment. Furthermore, five functional beneficial rhizosphere microbes including: Microbacterium sp., Pseudomonas extremaustralis, Bacillus amyloliquefaciens, Priestia megaterium, and Bacillus subtilis were isolated from the two treatments with the best remediation effect and synthetic communities (SynComs) were constructed. SynComs inoculation experiment further demonstrated the role of specific beneficial microbes in regulating the bioavailability of heavy metals. Results revealed that Se supplementation efficiently facilitated the phytoextraction of combined Cu–Cd–Cr contaminated soil, and B. proteolyticus SES inoculation showed the synergistical enhancement effect in the presence of Se. Graphical abstract: Image 1 Highlights: Se and B. proteolyticus SES enhanced the extraction of Cu, Cd, and Cr by ryegrass. Optimization of rhizosphere microenvironment and microbiome drive phytoremediation. Rhizosphere predominant taxa can promote plant growth and resist heavy metals. Functional beneficial microbes assist ryegrass to remediate Cu–Cd–Cr contamination.